Essay Error Analysis on the 1st Year Students of English Education Department - Mustakim Mustakim; Ita Sarmita Samad (Universitas Muhammadiyah Enrekang, 2019)
This study aimed to identify and describe the most common errors found in essay writing produced by first-year students of the English Education Department at STKIP Muhammadiyah Enrekang. The study employed a qualitative descriptive design. The data were collected through documentation of students’ essay assignments written over several weeks and then analyzed to classify the types and frequency of errors. The findings revealed that students still experienced substantial difficulty in producing accurate English essays. A total of 330 errors were identified and categorized into 24 error types. The most frequent problems appeared in articles, prepositions, spelling, meaningless sentences, word choice, subject-verb agreement, auxiliary verbs, plural forms, verb forms, and capital letters. The analysis also showed improvement after corrective feedback was provided, with the number of errors decreasing from 250 in the earlier essays to 80 in the later essays. These findings indicate that grammatical accuracy, lexical choice, and sentence construction remain major challenges for beginning EFL writers. The study concludes that error analysis is essential for helping lecturers identify learners’ difficulties and design more effective teaching materials, feedback practices, and writing instruction. More guided practice and explicit correction are recommended to improve students’ essay writing ability.